The Voting Rights Act After Shelby County v. Holder: A Potential Fix to Revive Section 5 - Thomas L. Brunell (Association Française d'Etudes Américaines, 2016)
The passage of the Voting Rights Act of 1965 (VRA) was a momentous occasion for minority voters in the United States, and its positive effects could be measured immediately. However, when Section 4 of the VRA was declared unconstitutional in Shelby County v. Holder (2013), the ability of the VRA to continue its protection of minority voters was called into question. We argue that the VRA is still necessary and propose an administrative notification system that could fix the issues with Sections 4 and 5.